Dorsal dermal sinus presenting as quadriparesis. Issue 6 (29th June 2019) - Majumdar, Ishita; Kundu, Ritabrata; Das, Joydeep; Mukherjee, Devdeep
Abstract : Dorsal dermal sinus (DDS) represents the spectrum of spinal dysraphism. Children may present with features of meningitis. A 13-month male child presented with features of meningitis and quadriparesis. Clinical examination revealed a small pit over the thoracic spine. MRI was suggestive of a DDS. Initially, the patient responded to antibiotics and methylprednisolone, which was given for resolving the mass effect. However, he had a recurrence of symptoms and underwent surgical exploration and resection of DSS with resolution of symptoms. Careful examination of the back is extremely essential in children with meningitis. Radiological investigation helps in visualisation of the DSS. Although rare in children, they may present with recurrent meningitis.